Partisipasi Katekis dalam Kerasulan Awam di Lingkungan Santo Yakobus Mayor Kalibago Barat - Angela Florida Mau; Intansakti Pius X (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
Catechist participation in lay apostolate in St. Yakobus Mayor Kalibago Barat, such as the areas of life testimony, social participation, contribution of energy, thoughts, are experiencing setbacks caused by a lack of awareness of being involved in the parish, a lack of sense of responsibility, a lack of sensitivity and concern for one another. The purpose of this study is to reveal and describe the concept catechist participation in the lay apostolate. In this study using a type of descriptive qualitative method, regarding catechist participation in lay apostolate. The data obtained in the study were collected through interviews and observation. The data collection system uses in-depth interviews with a number of informants involved in the Catechist participation process, and searches for documents related to participation in online mass media. The results of the study concluded that catechists are inseparable from the lack of awareness of involvement in the parish. Therefore, this research is conducted to make catechists aware of their role in carrying out their duties and responsibilities properly and correctly